FAIR TRADE: GO WITH THE FLO - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Having read the article in Spore 67 on 'Fair rewards for small farmers', Ndoung Albert, Coordinator of GERAD, BP 6847, Yaounde, Cameroun asked for the addresses of three of the fair trade organizations mentioned: Transfair, Fair Trade Foundation,...